2016
DOI: 10.7196/samj.2016.v106i11.12013
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence at a tertiary institution

Abstract: The extent of IPV among the medical and social work students sampled was found to be unacceptably high, both as victims and as perpetrators. As a result of their exposure to IPV, these individuals may have difficulty in managing patients who have been subjected to abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 16 publications
3
5
0
11
Order By: Relevance
“…These study findings are important because they not only add to the scant literature on dating violence among college students in Costa Rica, but the findings are also consistent with previous literature on the physical and mental health problems, including sexual consequences, exhibited by dating violence victims ( Amar & Gennaro, 2005 ; Ohnishi et al, 2011 ; Spencer et al, 2016 ).…”
Section: Discussionsupporting
confidence: 88%
“…These study findings are important because they not only add to the scant literature on dating violence among college students in Costa Rica, but the findings are also consistent with previous literature on the physical and mental health problems, including sexual consequences, exhibited by dating violence victims ( Amar & Gennaro, 2005 ; Ohnishi et al, 2011 ; Spencer et al, 2016 ).…”
Section: Discussionsupporting
confidence: 88%
“…Las manifestaciones psicológicas de tipo emocional se conceptualizan como una alteración del ánimo que conlleva a que la persona experimente diferentes sensaciones derivadas de las situaciones de la violencia en el noviazgo. Algunas manifestaciones que caen dentro de esta subcategoría son los sentimientos de depresión 31 , de culpa 3 y de vergüenza 3 . Finalmente, las manifestaciones en el autoconcepto tienen que ver con los cambios desfavorables en la forma en la cual una persona se visualiza y valora a sí misma como consecuencia de estar involucrada en una relación de violencia; se podrían señalar la pérdida de la integridad personal 27 y la baja autoestima 3 .…”
Section: Resultsunclassified
“…Algunas manifestaciones que caen dentro de esta subcategoría son los sentimientos de depresión 31 , de culpa 3 y de vergüenza 3 . Finalmente, las manifestaciones en el autoconcepto tienen que ver con los cambios desfavorables en la forma en la cual una persona se visualiza y valora a sí misma como consecuencia de estar involucrada en una relación de violencia; se podrían señalar la pérdida de la integridad personal 27 y la baja autoestima 3 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…International studies have shown that university students have a range of 26-84% of engaging dating violence and 29-30% have become subject to daing violence (Spencer, Haffejee, Candy, & Kaseke, 2016:1129Kamimura, Nourian, Assasnik, & Franchek-Roa, 2016-a:53;Umena, Fowole, & Adeoye, 2014:1;Chan etal.,2008:529;Amar, & Gennora, 2005:232;Straus, 2004:790).When the studies in Turkey on dating violence experience of university students are examined, Terzioğlu and colleagues (2016) stated that attitudes of university students were not supportive on dating violence, in his study on assessing prevalance of dating violence, Hatipoğlu (2010) stated students had higher levels of becoming subject to dating violence and increasing aggression levels in their dating relations (Terzioğlu et al, 2016:231;Hatipoğlu, 2010:4).Studies have shown that university students differ in terms of engaging and being subject to violence in dting relations of university students.This may be due to differences in the extent to which students can describe violence and be aware of the types of violence and can express the level of violence experienced.In our study, it was determined that 6.9% of the nursing students are subject to dating violence and 7.1% have become subject to violence.Similar to our findings, Er Güner (2016)in study on nursing students, states that 4.1% of the students report they have engaged violence to their partners (Er Güneri, 2016:52).In addition to these findings, in the study on nursing college students, Aslan and colleagues (2008) found that 21.6% of students were exposed to violence while 18.4% of them had engaged in violence,Conner and colleagues (2013) reported that 40% of nursing students were exposed to any type of violence in the partner relationship (Aslan et al, 2008:31,33;Conner et al,2013:236). When compared with the results of the research conducted in the field of literature, it can be said that nursing students have lower rates of engaging and exposing to dating violence.This may be related to the increased awareness of nursing education in the steps of prevention and intervention of violence.…”
Section: Discussionmentioning
confidence: 99%